2000
DOI: 10.1007/pl00001106
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Approach of Structuring by Fragmentation

Abstract: The paper addresses the problem of fingerprints of fragmentation processes, showing that structuring by fragmentation can be detected and investigated fruitfully if approached with a proper methodology, of which fractal instruments represent an important part. Studied aspects include fragments size distributions, fragments size-position relations, and long-range correlations in fracture profiles and fracture patterns. The choice of experiments (comminution of flat samples and fragmentation by desiccation crack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In the inner Sandhill Corner shear zone, B. R. found that the fragment size distribution defined two power-law trends (two slopes, or D-values, in a log-log plot) that intersect at a value of E s = ∼10 μm (Figure 4). Such "bifractal" distributions are observed in a wide range of different processes from drilling, brecciation, crushing, and milling of rock (Barnett, 2004;Carpinteri & Pugno, 2002;Farris & Paterson, 2007;Roy et al, 2012;Taşdemir, 2009) to rapid shock fragmentation of brick, glass, quartz, rock and ceramic (Barnett, 2004;Capaccioni et al, 1986;Davydova et al, 2014;Fujiwara et al, 1977;Hossain & Kruhl, 2015;Keulen et al, 2007;Roy et al, 2012;Suteanu et al, 2000). Bifractal distributions are sometimes interpreted as identifying a grinding limit (e.g., Keulen et al, 2007), but 10 μm is far too large for the grinding limit of garnet (∼0.26 μm for almandine-pyrope; B. R. .…”
Section: Fragment Sizes and Integration Length Scales Used In The Pre...mentioning
confidence: 99%
“…In the inner Sandhill Corner shear zone, B. R. found that the fragment size distribution defined two power-law trends (two slopes, or D-values, in a log-log plot) that intersect at a value of E s = ∼10 μm (Figure 4). Such "bifractal" distributions are observed in a wide range of different processes from drilling, brecciation, crushing, and milling of rock (Barnett, 2004;Carpinteri & Pugno, 2002;Farris & Paterson, 2007;Roy et al, 2012;Taşdemir, 2009) to rapid shock fragmentation of brick, glass, quartz, rock and ceramic (Barnett, 2004;Capaccioni et al, 1986;Davydova et al, 2014;Fujiwara et al, 1977;Hossain & Kruhl, 2015;Keulen et al, 2007;Roy et al, 2012;Suteanu et al, 2000). Bifractal distributions are sometimes interpreted as identifying a grinding limit (e.g., Keulen et al, 2007), but 10 μm is far too large for the grinding limit of garnet (∼0.26 μm for almandine-pyrope; B. R. .…”
Section: Fragment Sizes and Integration Length Scales Used In The Pre...mentioning
confidence: 99%
“…Turcotte and Anderson 1992;Yielding et al 1996). Although different data has been obtained in other experiments (Suteanu et al 2000), in this paper we adopted a value near the Sammis's model for fault length L distribution using the following equation…”
Section: Construction Of Datasetsmentioning
confidence: 99%
“…Figure 5 shows an example related to a crack pattern produced experimentally (axes are represented in base 2 logarithms). Starch suspension in water, poured on glass plates, was subject to dessication, and the resulting crack pattern was analyzed; details regarding the experimental conditions can be found in Suteanu et al, 2000. The points connected with a full line lead to v F = 1.58 ± 0.06.…”
Section: Scalementioning
confidence: 99%